New record of the cubomedusa Tamoya haplonema Müller, 1859 (Cnidaria: Scyphozoa) in the South Atlantic - Pastorino, Roberto Santiago Guido
Few papers record the presence of medusae in South Atlantic Ocean. Mianzan et al. (1988), Mianzan (1989) and Mianzan and Cornelius (1999) reported all bibliographic and personal findings of Scyphozoa in this part of the Atlantic. Cubomedusae are represented in the south Atlantic by apparently three species: Tamoya haplonema Müller, 1859, Chiropsalmus quadrumanus (Müller, 1859) and Carybdea atlantica Barattini & Ureta, 1960. However, the latter was mentioned only by the authors and disregarded by Mianzan et al. (1988) and Mianzan and Cornelius (1999). Mayer (1910, in Vanucci,1957) stated the range of T. haplonema to be from Santa Catarina, southern Brazil up to North Carolina, USA. Goy (1979) recorded two specimens of T. haplonema from 34°S off the Uruguayan coast. As far as I know this is the southernmost record of a cubomedusa in the Atlantic. Six specimens of the same species were collected by the Discovery Expedition in the Gulf of Guinea, Africa in 58–67 m depth (Stiasny, 1934) confirming its anfiatlantic distribution. This note records the southernmost finding of T. haplonema Müller, 1859 and its first occurrence in Argentine waters. Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina